High-Rise Buildings under Multi-Hazard Environment Assessment and Design for Optimal Performance - Huang, Mingfeng; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book discusses performance-based seismic and wind-resistant design for high-rise building structures, with a particular focus on establishing an integrated approach for performance-based wind engineering, which is currently less advanced than seismic engineering. This book also provides a state-of-the-art review of numerous methodologies, including computational fluid dynamics (CFD), extreme value analysis, structural optimization, vibration control, pushover analysis, response spectrum analysis, modal parameter identification for the assessment of the wind-resistant and seismic performance of tall buildings in the design stage and actual tall buildings in use. Several new structural optimization methods, including the augmented optimality criteria method, have been developed and employed in the context of performance-based design. This book is a valuable resource for students, researchers and engineers in the field of civil and structural engineering.
Introduction -- Overall view on performance-based engineering under multi-hazard environment -- A hybrid RANS and kinematic simulation of wind load effects on full-scale tall buildings -- Peak distributions and peak factors of wind-induced pressure processes on tall buildings -- Time-domain Dynamic Drift Optimization of Tall Buildings Subject to Stochastic Excitation -- Integrated structural optimization and vibration control for improving dynamic performance of tall buildings -- Performance-based design optimization of wind-excited tall buildings -- Structural dynamic and aerodynamic performance evaluation of a tall building -- Multi-hazard performance assessments of a high-rise building in Hong Kong.
Keywords: Civil engineering; Engineering mathematics; Engineering -- Data processing; Engineering design; Civil Engineering; Mathematical and Computational Engineering Applications; Engineering Design